Heave performance of a ballastless track subgrade of double line high-speed railway filled with micro-expansive andesite under water immersion. (20th August 2020) - Duan, Junyi; Yang, Guolin; Hu, Min; Wang, Gang; Lin, Yuliang
Highlights: Ballastless track subgrade filled with micro-expansive andesite was constructed. An experiment was carried out with the foundation immersed in water. Swelling characteristics of the foundation and deformation responses of subgrade were studied. Periodic fluctuation of heave of the subgrade was related to air temperature. Abstract: Due to the swelling–shrinkage behaviors of expansive fillings, railway subgrade defects in expansive soil regions are prominent, which are difficult to repair, easy to relapse and exist for a long time. Field investigation reveals that some micro-expansive fillings have the potential to construct the railway subgrade and then solve the shortage of railway fillings. However, the swelling characteristics of the railway subgrades filled with the micro-expansive fillings remain unclear. To solve the problem, this paper describes an indoor physical model experiment of a ballastless track-subgrade filled with micro-expansive andesite at 1:2 scale. By simulating the immersion of the foundation (area below the subgrade) in rising groundwater, the effects of the foundation swelling on the mechanical and deformation characteristics of the entire subgrade are analyzed. The results show that the railway subgrade undergoes heave deformation under water immersion, where a significant reduction is observed in the heave deformation from the foundation to the surface of the subgrade. For a double-line railway subgrade, the heave deformation of the foundation increases with horizontal distance from the subgrade centerline. It is also found that the heaves at the track slab and subgrade surface show cyclic fluctuations with a 24-hour cycle due to the periodic variations in the ambient temperature.